An Analysis of Students’ Ability in an Interpretive Listening Course - Kasriyati, Destina; Andriani, Refika; Herdi, Herdi (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
The world of education currently requires students to study from home through online learning because of the covid 19 pandemic. Online learning has been going on for almost 2 years so learning is no longer face-to-face. Students faced some problems when they should learn interpretive Listening courses through online learning. One of the problems such as; Students got some difficulties understanding the material. This is the concern of researchers to analyze studentsâ€™ learning outcomes in an interpretive listening course during online learning. This research approach uses descriptive quantitative utilizing descriptive statistics. There were 55 students who participated in this research. The data was gathered by an online test. The test is available at https://www.examenglish.com. The result suggests students had an average of score 69.4 of the total sample, namely 55 students. Then there is a minimum or lowest score of 30 and the highest is 77. This score has conversion based on score of the Common European Framework of Reference for Languages (CEFR). Therefore, it indicated that student learning outcomes in interpretive listening courses can be categorized as advanced. Where they have an advanced level in understanding and comprehending of listening activities.Â Even with limited facilities and sometimes unsupported internet networks, the learning outcome was running well.